EDUCATIONAL ENVIRONMENT OF HIGHER EDUCATIONAL INSTITUTION: SCIENTIFIC APPROACHES TO THE STRUCTURE - Іванова, Т. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article deals with the educational environment of higher educational institutions in the context of system approach in accordance with the indicators characterizing the system as an object of knowledge (integrity, structuring, hierarchy). The author focuses on the structure, i.e. on the definition of the composition, structure and organization of elements and parts of the system, identifying the leading interactions between them in the context of the educational environment of the university. The table provides various scientific approaches to the definition of the educational environment of the university. They proved not to deny each other, but only present different aspects of the studied phenomenon. Their analytical generalization is presented. The author’s structure of the educational environment of the university, which contains the strategic, socio-cultural, personal, value-semantic, subjective-business, communicative and technological component is presented